2023
DOI: 10.3389/fphar.2023.1138900
|View full text |Cite
|
Sign up to set email alerts
|

Yue-bi-tang attenuates adriamycin-induced nephropathy edema through decreasing renal microvascular permeability via inhibition of the Cav-1/ eNOS pathway

Abstract: Edema is one of the most typical symptoms of nephrotic syndrome. Increased vascular permeability makes a significant contribution to the progression of edema. Yue-bi-tang (YBT) is a traditional formula with excellent clinical efficacy in the treatment of edema. This study investigated the effect of YBT on renal microvascular hyperpermeability-induced edema in nephrotic syndrome and its mechanism. In our study, the content of target chemical components of YBT was identified using UHPLC-Q-Orbitrap HRMS analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Therefore, when PQ is absorbed into the bloodstream, it directly causes damage to vascular endothelial cells. It has been demonstrated that PQ exposure induces glutathione redox cycle dysfunction and excessive endothelial albumin permeability in microvascular endothelial cells ( 6 , 7 ). Therefore, identification of therapeutic agents that can maintain the endothelial barrier and attenuate pulmonary microvascular permeability may reduce mortality and improve prognosis, which is of great significance for the clinical treatment of PQ-induced acute lung injury (ALI), but its protective mechanism needs further study.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when PQ is absorbed into the bloodstream, it directly causes damage to vascular endothelial cells. It has been demonstrated that PQ exposure induces glutathione redox cycle dysfunction and excessive endothelial albumin permeability in microvascular endothelial cells ( 6 , 7 ). Therefore, identification of therapeutic agents that can maintain the endothelial barrier and attenuate pulmonary microvascular permeability may reduce mortality and improve prognosis, which is of great significance for the clinical treatment of PQ-induced acute lung injury (ALI), but its protective mechanism needs further study.…”
Section: Introductionmentioning
confidence: 99%